log [tex]\frac{x+4}{(x-3)^{2}}[/tex] по основанию 3-x [tex]\geq[/tex] -2
log (х+4)/(x-3)^2 по основанию 3-x ≥ -2
-2=-2log 3-xпо сновани. 3-x=log(3-х)^-2 по основанию з-х
log(3-х)^-2 по основанию з-х
log (х+4)/(x-3)^2 по основанию 3-x ≥log(3-х)^-2 по основанию з-х
(х+4)/((х-3)(х-3))1/((х-3)(х-3))
(х+4)/(х^2-6x+9)1/(х^2-6x+9)
x+41
x-3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
log (х+4)/(x-3)^2 по основанию 3-x ≥ -2
-2=-2log 3-xпо сновани. 3-x=log(3-х)^-2 по основанию з-х
log(3-х)^-2 по основанию з-х
log (х+4)/(x-3)^2 по основанию 3-x ≥log(3-х)^-2 по основанию з-х
(х+4)/((х-3)(х-3))1/((х-3)(х-3))
(х+4)/(х^2-6x+9)1/(х^2-6x+9)
x+41
x-3